Written mathematical communication accuracy on linear equation and inequality - Zahri, M; Budayasa, I K; Lukito, A (Journal of physics. Conference series, 2019)
Written mathematical communication is the process of sharing idea and mathematics understanding in written form. One of the qualified communication indicators is accuracy. Therefore, accuracy is considered to be one of the essential characteristics that pre-service mathematics teacher should have. This research implemented qualitative in nature aiming to describe the pre-service teachers' written mathematical communication accuracy in explaining one variable linear equation and inequality. The subjects were 20 pre-service mathematics students who were given mathematical communication task. Then, two subjects were chosen based on their preparation which classified as quite complete. The data was collected from lesson plan, presentation material, and teacher's note on whiteboard during the learning process. The data were analysed from each sentence containing mathematical language. The result of this research showed that both subjects could do written mathematical communication towards one variable linear equation and inequality accurately. This accuracy could be described by considering the accuracy of mathematical notation and terminology, the correct concept explanation, the procedure with clear and logical algebra manipulation, the calculation process, and also rigorous final result. However, the subjects could not explain logically the reason why the sign would change, if both sides of an inequality were multiplied by negative number.